Analysis of organochlorine pesticides levels in irrigation water from various water sources across Egypt - Khairy, Omar Tarek (AUC Knowledge Fountain, 2020)
Organochlorine pesticides are extensively used in agriculture to cope with the world’s increasing population and demands for nutrition. This class of pesticides poses a serious risk to human health upon chronic exposure to elevated levels. Determination of organochlorine pesticides levels in water has been extensively covered in literature in Egypt and other parts of the world. The need for up-to date data and statistical information regarding the levels of organochlorine pesticides in water is ever increasing. These compounds, although a lot have been prohibited from use decades ago, can still be detected in trace levels in water due to their long half-lives and bioaccumulation. This study contributes to the existing pool of data of pesticide levels in water and expands on it by assessing the levels in new sources of irrigation water and fish farms as well. All samples collected were extracted using Solid-Phase Extraction technique and analyzed using GC-ECD as well as GC-MS. Levels of 7 pesticides was determined and reported for both instruments. Among the 7 reported oc pesticides, heptachlor was found to be the most recurring with a frequency of detection of 52.9% in GC-ECD and 18.18% in GC-MS and mean values of 0.09 µg/l and 0.10 µg/l respectively. Mean values reported were found to be higher than the acceptable limit of WHO of 0.03 µg/l which indicates a significant level of pollution that requires future mitigation. o,p-DDD was not detected in any of the samples, while p,p-DDT was detected in only one sample with a value of 0.06 µg/l. This study indicates that although DDT was heavily used in the past decades in Egypt, its prohibition from the 1980s forward may have contributed to the decrease of its levels in the natural water resources to the point that its almost not detected in this study. Fish Farms (Tanks) marked the highest frequency of pesticides detection with 100% detection with GC-ECD and 33% detection with GC-MS. Mean values of total oc pesticides in GC-ECD for fish farms samples was 0.334 µg/l for GC-ECD and 1.484 µg/l for GC-MS, a possible evidence of bioaccumulation throughout the food chain.